Outbreak of typhoid fever in non-endemic area: comparison of three molecular typing methods - Gruner, E.; Flepp, M.; Gabathuler, U.; Thong, Kwai Lin; Altwegg, M. (Elsevier, 1997)
An outbreak of typhoid fever in Zurich, Switzerland, which involved seven customers and three employees of a city mall restaurant, was investigated by comparing three molecular typing methods: pulsed-field gel electrophoresis (PFGE), ribosomal RNA gene restriction patterns (ribotyping), and random amplified polymorphic DNA (RAPD). Both PFGE and ribotyping identified two molecular patterns among the outbreak-related isolates which differed in one band: these isolates were considered clonally related and differed clearly from other unrelated S. typhi strains. RAPD could not distinguish among outbreak isolates and control strains.